Intellectually Gifted Fifth Graders: Is Enriched Learning Practice Needed in Primary School? - Shumakova N.B. (Психолого-педагогические исследования, 2022)
The article presents the results of a study of the features of cognitive development and learning motivation of intellectually gifted and normotypical fifth-graders who studied in the primary grades according to programs of various types – enriched and traditional (typical). Using the two-way MANOVA analysis of variance, we tested the assumption about the influence of primary school education on the cognitive development and learning motivation of intellectually gifted and normotypical fifth-graders (N=150). Research methods: "Standard Progressive Matrices" by Raven, computerized tests for diagnosing basic cognitive characteristics (number sense, working memory and information processing speed) Tikhomirova T.N. and Malykh S.B., the author's technique "Figurative and verbal creativity", "Scale of educational motivation" Gordeeva T.O. It was revealed that intellectually gifted fifth-graders, regardless of the educational program, are characterized by higher rates of intrinsic cognitive motivation, intelligence, sense of number and speed of information processing compared to their normotypical peers. It is shown that "giftedness" and not the "educational program", affects the sense of number and the speed of information processing, while the influence of the factors "giftedness" and "educational program" on indicators of learning motivation was not found. The type of education in elementary school is critical to the development of the creative potential of intellectually gifted children. In enriched learning, gifted children demonstrate significantly higher levels of verbal and figurative creativity than their gifted peers in traditional learning. With respect to normotypical peers, no significant positive effects of enriched learning on creativity indicators were found.